Land use, land-use change, and forestry (Published for the Intergovernmental Panel on Climate Change [by] Cambridge University Press, 2000)
The exchange of carbon between the atmosphere and biosphere is an important factor in controlling global warming and climate change. Consequently, it is important to examine how carbon flows between different pools and how carbon stocks change in response to afforestation, reforestation, and deforestation, and other land-use activities. This IPCC Special Report is a comprehensive, state-of-the-art examination of the scientific and technical implications of carbon sequestration and the global carbon cycle. It also examines environmental and socioeconomic issues, conservation, sustainable resource management, and development issues in relation to carbon sequestration. The volume will be invaluable for government policymakers, business/industry analysts and officials, environmental groups, and researchers in global change, atmospheric chemistry, soil science, and economics